In Bacillus subtilis, the Sirtuin Protein Deacetylase, Encoded by the srtN Gene (Formerly yhdZ), and Functions Encoded by the acuABC Genes Control the Activity of Acetyl Coenzyme A Synthetase - Gardner, Jeffrey G. (American Society for Microbiology (ASM), 2009)
This report provides in vivo evidence for the posttranslational control of the acetyl coenzyme A (Ac-CoA) synthetase (AcsA) enzyme of Bacillus subtilis by the acuA and acuC gene products. In addition, both in vivo and in vitro data presented support the conclusion that the yhdZ gene of B. subtilis encodes a NAD(+)-dependent protein deacetylase homologous to the yeast Sir2 protein (also known as sirtuin). On the basis of this new information, a change in gene nomenclature, from yhdZ to srtN (for sirtuin), is proposed to reflect the activity associated with the YdhZ protein. In vivo control of B. subtilis AcsA function required the combined activities of AcuC and SrtN. Inactivation of acuC or srtN resulted in slower growth and cell yield under low-acetate conditions than those of the wild-type strain, and the acuC srtN strain grew under low-acetate conditions as poorly as the acsA strain. Our interpretation of the latter result was that both deacetylases (AcuC and SrtN) are needed to maintain AcsA as active (i.e., deacetylated) so the cell can grow with low concentrations of acetate. Growth of an acuA acuC srtN strain on acetate was improved over that of the acuA(+) acuC srtN strain, indicating that the AcuA acetyltransferase enzyme modifies (i.e., inactivates) AcsA in vivo, a result consistent with previously reported in vitro evidence that AcsA is a substrate of AcuA.